2006
DOI: 10.1093/rheumatology/kel144
|View full text |Cite
|
Sign up to set email alerts
|

Are rheumatologists' treatment decisions influenced by patients' age?

Abstract: Our findings suggest that rheumatologists' treatment recommendations may be influenced by age. Future educational efforts should increase physician awareness of this possible bias in order to ensure equal service delivery across ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 25 publications
6
48
1
1
Order By: Relevance
“…Another factor leading to less aggressive treatment in older RA patients may be physician preference. 34 We also observed that patients in the South were more likely to initiate treatment with TNF-α inhibitors. Ours is the first study to document regional variations in the initiation of treatment with TNF-α inhibitors.…”
Section: Limitationsmentioning
confidence: 54%
“…Another factor leading to less aggressive treatment in older RA patients may be physician preference. 34 We also observed that patients in the South were more likely to initiate treatment with TNF-α inhibitors. Ours is the first study to document regional variations in the initiation of treatment with TNF-α inhibitors.…”
Section: Limitationsmentioning
confidence: 54%
“…Thirteen studies focussed on cardiac conditions, of which ten specifically explored medication underutilisation in atrial fibrillation. Four studies investigated the influence of patient age on clinicians' treatment decisions (Hajjar et al, 2002;Fraenkel et al, 2006;Harries et al, 2007;Kievit et al, 2010).…”
Section: Number and Type Of Studiesmentioning
confidence: 99%
“…Studies investigating clinicians' understanding of 'old age' have focused on the management of rheumatoid arthritis (Fraenkel et al, 2006;Kievit et al, 2010), angina (Harries et al, 2007), and hypertension (Hajjar et al, 2002). Studies have revealed health professionals' biased understanding of 'old age' (Hajjar et al, 2002;Fraenkel et al, 2006;Harries et al, 2007), and that some physicians regard 'old age' a contraindication to treatment (Harries et al, 2007).…”
Section: Clinicians' Understanding Of 'Old' Agementioning
confidence: 99%
See 2 more Smart Citations